Enhancing electrochemical performance of Fe2O3 via in situ sulfurization and carbon coating modification for nickel-iron rechargeable batteries. (10th November 2018) - Li, Jin; Wang, Shulin; Chen, Xuelin; Xiao, Ting; Tan, Xinyu; Xiang, Peng; Jiang, Lihua
Abstract: The passivation issue of Fe2 O3 electrode has triggered off their low practical capacity, poor rate capability and cycling performance and thus limited their practical application as anodes for alkaline Ni-Fe batteries. This paper proposes a dual modification of Fe2 O3 by in-situ sulfurization and post carbon coating. Fe2 O3 -S nanorod arrays with a uniform sulfurization layer coated on Fe2 O3 core were firstly fabricated by in-situ sulfurization of Fe2 O3 nanorod arrays grown on Ti foil. After coating carbon on the Fe2 O3 -S arrays by PECVD process, Fe2 O3 -S@C were obtained. Electrochemical tests in alkaline electrolyte in the potential window of −1.2∼0 V show that the Fe2 O3 -S@C exhibited dramatically improved discharge capacity (60.5 times compared to Fe2 O3 ), cycling stability (92.2% for Fe2 O3 -S@C and only 7.9% for Fe2 O3 -S after 100 cycles) and excellent rate capability, owing to the co-contribution of the sulfurization layer and carbon layer. Furthermore, a Ni-Fe cell is assembled by pairing with a Ni2 S3 cathode, and delivers high energy/power density (45.64 Wh/kg at 1.3 kW/kg and 27.14 Wh/kg at 10.3 kW/kg).